Comparison of Antihyperlipidemic Activity Temu Mangga’s Rhizomes and Ketepeng Cina’s Leaves Infusion: Perbandingan Aktivitas Antihiperlipidemia Infusa Rimpang Temu Mangga dan Daun Ketepeng Cina - Nugraha, Dyan; Noor Wildiati Magfirah; Novia Henjani (Journal of Pharmacy and Science, 2021)
Statins are first line therapy of antihyperlipidemia. It reduced LDL levels more than 50%. However, a serious side effects such as rhabdomyolisis which can lead to kidney failure. On other side, people often consumed boiled water of Temu Mangga’s Rhizome and/or Ketepeng Cina’s Leeaves as antihyperlipidemic. Both of them has a potential as adjuvant therapy. Purpose: To compare antihyperlipidemic activity of Temu Mangga’s Rhizome and Ketepeng Cina’s Leaves as alternative treatment. Method : Test animals were induced with High Fat Diet Food (HFDF) for the first 15 days, and with Temu Mangga’s Rhizome and Ketepeng Cina’s Leaves for the next 15 days. Study group: Simvastatin (positive control), Na CMC 0.5% (negative control), 450 mg/Kg BW; 900 mg/Kg BW; 1.800 mg/Kg BW of Temu Mangga’s Rhizome and 225 mg/Kg BW; 450 mg/Kg BW; and 900 mg/Kg BW Ketepeng Cina’s Leaves. Results: Temu Mangga 360 mg/200 gram BW was not significantly different from positive control in reducing total cholesterol, triglycerides, LDL and increasing HDL. Ketepeng Cina’s Leaves 180 mg/200 gram BW had the best effect, but it was not comparable to the positive control. Conclusion: 1.800 mg/Kg BW Temu Mangga’s Rhizome showed better antiyperlipidemic activity than 900 mg/Kg BW Ketepeng Cina’s Leaves.